Synopsis and lectotypification of Distimake rhyncorhiza (Dalzell) Simões & Staples (Convolvulaceae): a little known species from the Western Ghats (India) - Simões, Ana Rita; More, Sushant (Phytotaxa, 2018)
We present a synopsis of a rare and little-known species of Distimake from Western India: a complete morphological description based on recent collections is provided, and nomenclature and typification issues are resolved. The fruit and seeds are described for the first time. With new morphological evidence and a full characterization of D. rhyncorhiza, the present study corroborates its placement in Distimake and supports its identity as a distinct species. The conservation status is assessed as Endangered but its distribution range is not yet fully documented and this assessment might be reviewed if more collections are made.